2017
DOI: 10.5152/tjbh.2017.3266
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptation of the Short-Form Supportive Care Needs Survey Questionnaire (SCNS-SF 34) into Turkish

Abstract: IntroductionDetermining and managing the unfulfilled supportive care needs of the patients is among the base components of healthcare (1). Supportive care may be considered as the determination of the care needs of the patients with and patient-centered approach and fulfilling those needs effectively (2). Before and during diagnosis, throughout the treatment, in the terminal period, it is the supportive care that helps the patient and the family to cope with the illness (3).Breast cancer is the most common can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
2
26
1
Order By: Relevance
“…Previous translation of the survey showed variability in terms of the factorial structure used in different settings. The study conducted in Turkey has demonstrated that the four-factor was the best model to adapt in Turkish society for the determination of the supportive care needs of breast cancer patients [17]. It was supported by a study by Au et al, where the four-factor was the best final model.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Previous translation of the survey showed variability in terms of the factorial structure used in different settings. The study conducted in Turkey has demonstrated that the four-factor was the best model to adapt in Turkish society for the determination of the supportive care needs of breast cancer patients [17]. It was supported by a study by Au et al, where the four-factor was the best final model.…”
Section: Introductionmentioning
confidence: 83%
“…Since the 34-items short-form Supportive Care Needs Survey (SCNS-SF34) was developed, it has been translated and validated in many other languages to further confirm the psychometric properties of the translated version among a mixed group of cancer patients in different cultural settings [9,[12][13][14][15]17]. To the best of our knowledge, this was the first study to assess the factorial structure of the Malay version of the SCNS-SF34 involving Malay-speaking cancer patients with various diagnoses using the confirmatory factor analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, the questionnaire can also be used to determine the number of perceived unmet needs (scores of 3 or more is considered an unmet need). The survey can be applied by interviews with the individuals on the phone [ 22 , 23 ]. Besides, the participants were asked whether they needed to be informed regarding COVID-19 (Yes/No).…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate higher supportive care need in that aspect. As an alternative use, the questionnaire can also be used to determine the number of the perceived unmet needs (3 or higher scoring is considered unmet need) [9]. In addition, participants were asked how much they needed to be informed regarding COVID-19 (no need -a little needed -quite needed -very much needed).…”
Section: Supportive Care Needsmentioning
confidence: 99%